Pediatric adnexal torsion - from presentation to outcomes: a 5 years experience of a tertiary center in Bahrain - Husain, Sara; Alqubaiti, Zainab; Ayoub, Barrak; Haider, Fayza (International Surgery Journal, 2024)
Background: This study aims to explore the clinical signs, diagnostic methods, and surgical treatments of adnexal torsion in children under 14. The study included 19 children, with an average age of 12, who presented with severe abdominal pain leading to a diagnosis of adnexal torsion. Methods: We conducted a retrospective review of pediatric patients who underwent surgery for suspected adnexal torsion at a pediatric surgery center from January 2018 to December 2022. Data collected included age, symptoms, diagnostic tests, surgical details, and histopathology results. Results: The predominant symptoms were abdominal pain, vomiting, nausea, and elevated white blood cell counts in about 50% of the cases. Laparoscopy was the initial approach in 68.4% of cases, with 21.1% requiring conversion to open laparotomy. Ovarian-sparing surgery was performed in 73.7% of the cases, while oophorectomy was necessary in 26.3%. Most histopathological examinations disclosed benign ovarian cysts, including simple cysts, serous cystadenomas, and mature cystic teratomas, often complicated by torsion and leading to ovarian infarction. Younger patients and those with higher leukocyte count found to have higher rates of oophorectomy. Conclusions: Adnexal torsion, although rare and challenging to diagnose in children due to non-specific symptoms such as abdominal pain, vomiting, and nausea, necessitates prompt recognition and management to minimize severe complications. Awareness among clinicians is crucial for early diagnosis and treatment, significantly impacting long-term outcomes.